Combining Killed Vaccine Candidate with Different Adjuvants to Determine Prophylactic Potential against Leishmaniasis - Kelleci, Kuebra; Allahverdiyev, Adil; Bagirova, Melahat; Ihlamur, Murat; Abamor, Emrah Sefik (SPRINGER INT PUBL AG, 2024)
Visceral Leishmaniasis is a serious public health problem caused by Leishmania species parasites. Approximately 500 thousand people get Visceral Leishmaniasis (VL) every year. An effective and reliable vaccine against the disease has still not been formulated. Choosing the right adjuvant is important to increase immunogenicity in vaccines prepared with total antigens. In this study, we investigate the ideal adjuvant for use in vaccine formulations against VL. For this purpose, Leishmania antigens (FTLA) obtained from L. infantum parasites by the freeze-thaw method and three different adjuvants (alum-saponin and calcium phosphate) were used. The effectiveness of the formulations was investigated in vitro by cell viability analysis and determination of nitric oxide and cytokine production abilities in J774 macrophage cells. According to the study results, it was determined that formulations prepared with calcium phosphate produced 72% more NO and approximately 7.2 times more IL-12 cytokine. The results obtained showed that calcium phosphate salts can be used as ideal adjuvants in vaccine research against leishmaniasis.
Keywords: Leishmaniasis; Calcium phosphate; Adjuvant; Vaccine; VISCERAL LEISHMANIASIS; CHAGASI INFECTION; BALB/C MICE; ANTIGEN; PROTECTION; Parasitology; Veterinary Sciences; Zoology